Strategi Pustakawan dalam Mengembangkan Literasi Siswa Tunarungu di SLB Taman Pendidikan Islam Medan - Pitri, Eka Nursah; Nurhayani, Nurhayani; Ismail, Ismail (Comit: Communication, Information and Technology Journal, 2025)
This research was conducted at the Library of SLB Taman Pendidikan Islam Medan. The aim of this study was to identify the factors causing low literacy among deaf students and to explore the librarian's strategies in developing literacy beneficial for Deaf students at SLB Yayasan Taman Pendidikan Islam Medan. The research approach used in this study was descriptive qualitative. Based on the research findings, there are several factors contributing to the low literacy among deaf students at SLB Taman Pendidikan Islam Medan. One significant factor is the limited access to reading materials suitable for the students' needs. Deaf students often face challenges in accessing literacy resources that could support their learning, which can hinder their literacy development, considering the importance of access to reading materials appropriate for their comprehension level. The research also indicates that librarians at SLB Taman Pendidikan Islam Medan have implemented various effective strategies to enhance the literacy of deaf students. One successful strategy is collaboration between librarians and educators at the school. Librarians collaborate with teachers to integrate literacy into the curriculum and lesson plans, ensuring that literacy activities are not separated from the core subjects but become an integral part of students' educational experiences. This collaboration enables librarians to support teachers in providing relevant reading resources and supporting learning objectives. Thus, this conclusion underscores the important role of librarians in addressing factors contributing to the low literacy among deaf students with appropriate strategies. Collaborative efforts between librarians and educators are also a positive step in enhancing the literacy of deaf students at SLB Taman Pendidikan Islam Medan. This conclusion can serve as a basis for further improvements in literacy education for deaf students at the school.